The mechanism and efficacy of improving the auditing process in Bangladesh: a study on bank audit - Ridam, Md. Sadab Rahaman (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.